#TITLE_ALTERNATIVE# - SYAHRI FATHONI (NIM : 12011006), HILMAN
Arsenic (As), Boron (B), and F (Fluorin) have been long known as natural contaminants in geothermal fluid. This study was conducted to determine their concentrations in geothermal water and rocks, as well as factors that contribute to their occurrences in geothermal system. There were three geothermal fields studied which included Gunung Lawu Volcanic Geothermal Field, Lainea Non-volcanic Geothermal Field, and Dieng Volcanic Geothermal Field. The analysis of geothermal system as well as local geology from each field was carried out before conducting the geochemical analysis of water and rock. The study reveals that concentration of As and F are relatively similar both in volcanic rocks (host rock of the Gunung Lawu Field) and sedimentary and metamorphic ones (host rock of the Lainea Field). The concentration of As in geothermal water from the volcanic system is found higher compared to its non-volcanic counterpart. It is also inferred that sedimentary and metamorphic rocks contain higher amount of B than the volcanic rocks. Meanwhile, the concentration of B in geothermal water from the volcanic system is then found to be higher than the non-volcanic one. In comparison with other fields, the geothermal water of Dieng has anomalously higher As and B. The analysis shows that the occurrence of As, B, and F is not only affected by the source and water-rock interaction but also by processes, such as boiling, mixing, as well as condensation and leaching.